Pattern Recognition 32nd DAGM Symposium, Darmstadt, Germany, September 22-24, 2010. Proceedings - Goesele, Michael.; Roth, Stefan.; Kuijper, Arjan.; Schiele, Bernt.; Schindler, Konrad. (Lecture Notes in Computer Science,, 2010)
This book constitutes the refereed proceedings of the 32nd Symposium of the German Association for Pattern Recognition, DAGM 2010, held in Darmstadt, Germany, in September 2010. The 24 revised full papers and 34 revised poster papers were carefully reviewed and selected from 134 submissions. The papers are organized in topical sections on geometry and calibration, recognition, learning and optimization, applications, motion, low-level vision and features, as well as on surfaces and materials.